Effect of Consulting on Microcredit Repayment in Korea - 오윤해 (14255, 2015)
This study examines the effect of a one-on-one outsourced pre-lending consulting service on the repayment behavior of microcredit borrowers in Korea with administrative data from the Smile Microcredit Bank. A random change in the cut-off loan amount for m